2016
DOI: 10.1111/ijfs.13181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different cooking methods on some chemical and sensory properties of Galega kale

Abstract: Summary Kale (Brassica oleracea L. var. acephala) is rich in bioactive phytochemicals such as phenolic compounds and vitamins. However, cooking the plants can cause important changes in composition. The objective of this study was to investigate the effect of some domestic cooking processes (boiling, steaming, microwaving and pressure cooking) on several quality parameters of Galega kale. Boiling had the strongest effect on the antioxidant capacity (the IC50 was four times higher than in the fresh sample), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…All cooking treatment caused a significant increase in total sugars content with levels of 17.30 %, 24.56 % and 46.25 % in baked, grilled and fried tomato, respectively. In fact, Maceiras et al (2007); Armesto et al (2016) and De Santiago et al (2018) reported that the sugar content in some fruits and vegetables increase during cooking, which confirms the values obtained in our study. According to De Santiago et al (2018) heat treatment induces depolymerisation and the rupture of some glycosidic linkage in dietary fiber polysaccharides that favor the observed increase in carbohydrates.…”
Section: Physico-chemical Properties Of Fresh and Cooked Tomatoessupporting
confidence: 92%
See 1 more Smart Citation
“…All cooking treatment caused a significant increase in total sugars content with levels of 17.30 %, 24.56 % and 46.25 % in baked, grilled and fried tomato, respectively. In fact, Maceiras et al (2007); Armesto et al (2016) and De Santiago et al (2018) reported that the sugar content in some fruits and vegetables increase during cooking, which confirms the values obtained in our study. According to De Santiago et al (2018) heat treatment induces depolymerisation and the rupture of some glycosidic linkage in dietary fiber polysaccharides that favor the observed increase in carbohydrates.…”
Section: Physico-chemical Properties Of Fresh and Cooked Tomatoessupporting
confidence: 92%
“…These results are consistent with those reported in our study on the eggplant and we found that frying increase the acidity with a rate of 33.33% but baking decrease it with a percentage of 25.80% (Arkoub-Djermoune et al, 2016) which may be due to the degradation of certain organic acids during cooking, mainly citric acid. Indeed, they can also react with sugars during cooking by the condensation Maillard reaction, thus leading to the formation of brown polymers (Armesto et al, 2016) confirming the increase in non-browning enzymatic in the fried sample. However, the increase in acidic content recorded in fried tomato can be due to greater extraction of organic acids after softening of the cell wall by heat treatment and/or attributed to the reduction the water content which leads to an increase in the pH value.…”
Section: Physico-chemical Properties Of Fresh and Cooked Tomatoesmentioning
confidence: 56%
“…[40] Total Chl content was decreased by almost 79.82 to 91.23% depending on the MW output powers used (Figure 1b). Armesto et al [21] determined that reduction of total Chl content in Galega kale (Brassica oleracea L. var. acephala) ranged between 47.34 and 52.67% in MW application at 900 W. The reason of Chl content reduction is due the fact that Chl are degraded to undesirable gray-brown compounds like pheophorbide or pheophytin and further metabolizes to colorless compounds because of heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Quality loss involves both of taste changes and nutrients degradation. [14,15] Many research studies have been devoted to assess the way that MW processing affects the nutrient properties of vegetables such as ready to eat vegetables [16] , broccoli [17] , green beans, broccoli, and asparagus [18] , peas, carrot, spinach, cabbage, cauliflower, and turnips [19] , potato, carrot, onion, broccoli, and white cabbage [20] , Galega kale [21] , brown mustard [22] , and York cabbage. [14] The results on the effects of MW processing on the various nutrients of vegetables reported by various authors and they differ from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also assessed quality in kale and kale products directly (Albornoz, ; Kobori, Huber, Sarantópoulos, & Rodriguez‐Amaya, ; Kopsell et al., ; Sistrunk, ), but few studies to date have integrated sensory analysis in the interpretation of their results. Studies evaluating the effect of cooking methods (Armesto, Gómez‐Limia, Carballo, & Martínez, ) and production practices (that is, nitrogen, sulfur, and frost treatments) (Groenbaek et al., ) are some of the few that have included trained sensory panels, though lexicons were not standardized and only a small number of cultivars were included in each sample set.…”
Section: Introductionmentioning
confidence: 99%